Sulforaphane attenuates dextran sodium sulphate induced intestinal inflammation via IL-10/STAT3 signaling mediated macrophage phenotype switching - Yuyang Sun; Jiqing Tang; Cui Li; Jun Liu; Haijie Liu (Food Science and Human Wellness)
Innate immunity, particularly macrophages, is critical for intestinal homeostasis. Sulforaphane, a dietary isothiocyanate from cruciferous vegetables, has been reported to protect against intestinal inflammation. However, the role of macrophages in sulforaphane mediated intestinal inflammation and the underlying molecular mechanisms have not been studied yet. In this study, sulforaphane effectively attenuated dextran sodium sulphate (DSS) induced intestinal inflammation in murine model. Of note, sulforaphane skewed the switching from classically (M1) to alternatively (M2) activated phenotype both in intestinal and bone marrow-derived macrophages (BMDMs). The expression levels of M1 associated maker genes induced by DSS or lipopolysaccharide (LPS) plus interferon gamma-γ (IFN-γ) were suppressed by sulforaphane while M2 marker gene expression levels were improved. This resulted in alteration of inflammatory mediators, particularly interleukin-10 (IL-10), both in colon tissues and culture medium of BMDMs. Subsequently, IL-10 was found to mediate the sulforaphane induced M2 phenotype switching of BMDMs through the activation of STAT3 signaling. This was confirmed by immunofluorescence analysis with increased number of p-STAT3-positive cells in the colon sections. Moreover, anti-IL-10 neutralizing antibody significantly interfered M2 phenotyping of BMDMs induced by sulforaphane with reduced STAT3 phosphorylation. Findings here introduced a potential utilization of sulforaphane for intestinal inflammation treatment with macrophages as the therapeutic targets.